Unity Power Factor at the Power Supply Side for MATRIX Converter Fed PMSM Drives - Farhad Safargholi (Institute of Advanced Engineering and Science, 2014)
To reduce the high harmonic components at the main power supply current and to improve the input voltage distortion for matrix converter, design of input filters characteristics for matrix converter system is very important. Also, the input filter can be applied to the near unity power factor operation at the input side. It can be used to improve the power quality of the input current. This paper represents a direct space vector modulation (SVM) method and introduces switching patterns for SVM method and then design of input filter to compensate the power factor is analyzed. Simulation results with inductive load (RL) and Permanent-magnet synchronous motor (PMSM) are shown to validate the effectiveness of the proposed method.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4813